Analysis and Application of Single-Phase Controlled Rectifier in Half-Wave AC Motor Systems: Empowering Technical Education - Arya Adiansyah Saputra (Politeknik Perkapalan Negeri Surabaya, 2023)
This study explores the regulation of single-phase motor rotation through various methods, including adjusting motor frequency, voltage, resistance, and increasing the number of motor poles. Utilizing a stable oscillator circuit, the frequency parameters of a single-phase motor can be controlled by modifying the variable resistor value. A thyristor-based trigger circuit is employed to manage the motor's rotational speed by adjusting the trigger phase angle, which directly influences frequency and motor speed. Simulations conducted using PSIM software demonstrate the relationship between variable resistor adjustments and changes in motor rotation frequency. These simulations analyze the rotational behavior of single-phase motors based on the transformer output voltage, providing a foundational understanding of electronic circuit functionality. By leveraging PSIM, this study minimizes potential failures in practical circuit applications, contributing to enhanced technical education and skill development. The findings have significant implications for community-based technical training programs, equipping individuals with practical knowledge in electronic motor control systems and fostering community empowerment through applied technical education.